RENEWABLE ENERGY SOURCES: THE MAIN PILLAR OF THE GREEN ECONOMY (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
In the context of global climate change and increasing environmental degradation, the transition to a green economy has become a strategic priority for many nations. Renewable energy sources—such as solar, wind, hydro, and biomass—play a central role in this transformation. As the backbone of sustainable development, these clean energy alternatives offer a viable solution to reducing greenhouse gas emissions, decreasing dependency on fossil fuels, and fostering economic resilience.